Effect of Mental Toughness and Employee Experience on Organizational Commitment Amongst Workers in Toka Tindung Gold Mine Project, North Sulawesi - Maria Dyah Kusumawardhani; Oliandes Sondakh (Journal of World Science, 2026)
In recent years, the increasing tendency of professional workers, particularly Generation Z, to change jobs has raised concerns regarding organizational commitment. This study aims to examine the effects of mental toughness and employee experience on organizational commitment, with psychological well-being and work engagement as mediating variables, among employees at the Toka Tindung Gold Mine Project in North Sulawesi, Indonesia. This research employs a quantitative approach using a cross-sectional survey design. Data were collected through structured questionnaires distributed to 118 employees and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results reveal that mental toughness is the most significant predictor of organizational commitment, demonstrating strong direct effects on psychological well-being, work engagement, and organizational commitment. In contrast, employee experience shows a significant effect only on work engagement but does not directly influence organizational commitment. Furthermore, psychological well-being and work engagement are not found to mediate the relationship between mental toughness or employee experience and organizational commitment. These findings highlight the dominant role of personal resilience over organizational factors in shaping employee commitment, particularly within high-risk industries such as mining. The study provides both theoretical and practical contributions by emphasizing the importance of strengthening employees’ mental toughness to enhance organizational commitment and suggesting that organizations should integrate psychological resilience development into human resource strategies.